Vaccination against pertussis in Latin American preterm and low-birth weight infants: experts opinion position for a neglected childhood age group - María L Avila-Agüero; Sebastián Ospina-Henao; Cristina Mariño; Mirella Vázquez-Rivera; Juan Pablo Torres; Dora Estripeaut; Rolando Ulloa-Gutierrez; Angela Gentile (Expert Review of Vaccines, 2023)
Background Pertussis remains as one of the oldest leading vaccine-preventable diseases of childhood, despite many decades of primary vaccine doses and boosters’ implementation. Although the epidemiology is well understood in infants and children, premature babies and low-birth weight infants remain a special group where the disease incidence is unknown, severity of the disease is considerable, and specific vaccination recommendations are scarce. Research design and methods Retrospective review of the available evidence of pertussis vaccination in premature and low birth weight infants was analyzed from January 2000 to December 2022 in six selected countries: Argentina, Mexico, Colombia, Panamá, Costa Rica, and Chile. Results Although information on pertussis epidemiology, outbreaks, immunization schedules, rates of coverages, and awareness of the importance of vaccinating premature infants as a high-risk group, no specific information was available from the six analyzed countries for premature infants in terms of vaccine coverage rates and side effects in most countries. Chile had reports of adverse effects associated with vaccination of premature infants with the pentavalent vaccine, and their rationale to switching to hexavalent vaccine. Colombia had reports of the justification for the use of hexavalent vaccine in prematures in the Neonatal Units and Kangaroo Mother Programs throughout the country. Mexico had selected publications of the vaccination status in prematures and low-birth weight infants. Conclusion Despite its importance, increased morbidity, and highest risk of complications in premature babies, there is paucity of information of vaccine recommendations and coverage rates among selected Latin American infants.